Reading Comprehension Test and Its Challenges In Students’ Perspective - Sutrisno Sadji Evenddy; Ledy Nurlely; Marfu'ah Marfu'ah (English Education Department, 2021)
There are two objectives of this research were first, to find the most difficult question category that students faced in reading test, and last, to investigate the causes of students' difficulties. This research used a qualitative method and it was conducted at the first semester students of c class English Department of UNTIRTA year 2019. The descriptive method was used to expose the result of this research. The data were collected through documents of reading comprehension final test first semester and an interview with the students. The document was used to find out the most difficult question category, and the result after analyzing the document is the students got difficulties in answering the question about vocabulary mastery. It is also supported by the result of interviewing the students. There were 17 students from 20 students or 85% felt that the vocabulary question category in part B was difficult. Then, the interview was also used to investigate the causes of the student's difficulties in reading test. The result got after analysis, the causes of the students got difficulties and confused to answer vocabulary question because they were lack of vocabulary mastery, and their reading habit was poor. So, it indicates that students’ capability of guessing meaning some unfamiliar vocabulary or words in the current context needs to be improved.